The Influence of Teamwork, Work Motivation, and Work Discipline on the Performance of Medical Record Employees RSUD Dr. Haryoto Lumajang - M Khoirul Anwarudin Broto Suharto (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to determine the Effect of Teamwork, Work Motivation, and Work Discipline on the Performance of Recording Employees at Dr Haryoto Lumajang Hospital. This study uses quantitative methods with multiple linear regression analysis techniques. Respondents in this study were all medical record employees of Dr Haryoto Hospital Lumajang which totalled 36 people. Respondents were selected using saturated sample technique. Data collection using a questionnaire consisting of three independent variables, namely Teamwork, Work Motivation, and Work Discipline and one dependent variable, namely Employee Performance. Data were analysed using SPSS (Statistical Program for Social Science). The results of this study indicate that Teamwork has no significant effect on the Performance of Recording Employees of RSUD Dr. Haryoto Lumajang, Work Motivation has a significant effect on the Performance of Recording Employees of RSUD Dr. Haryoto Lumajang, and Work Discipline has a significant effect on the Performance of Recording Employees of RSUD Dr. Haryoto Lumajang.